The Influence Of Transformational Leadership and Work Meaningfulness On Innovative Behavior - Paulus Yasmin; Hanif Aulawi (CAKRAWALA : Management Science Journal, 2024)
This study aims to assess the influence of transformational leadership and job meaningfulness on the innovative behavior of employees at the Human Resources Development Agency for Industry (BPSDMI) under the Ministry of Industry of the Republic of Indonesia. A quantitative research method with total sampling was used, involving all 69 BPSDMI employees. Data were collected through questionnaires and analyzed using T-tests and multiple linear regression with SPSS. The results showed that transformational leadership and job meaningfulness have a positive but not significant effect on employees' innovative behavior. This indicates that although transformational leadership and job meaningfulness can enhance innovative behavior, their influence is not significant enough. Recommendations are given to BPSDMI leaders to increase engagement and provide clear direction to employees to foster workplace innovation.